Pembinaan dan penilaian kesesuaian modul pembelajaran kendiri alat muzik yangqin untuk pendidikan muzik tingkatan empat, kurikulum bersepadu sekolah menengah Malaysia - Chang, Yun Ping (Universiti Malaysia Sarawak (UNIMAS), 2007)
The study was conducted to develop and evaluate the applicable of self-learning module on the techniques of playing Yangqin as a music subject for form four sylabbus. Model Teras-Cabang Shaharom (1994) instructional design model was applied to develop this module. This study gained the data through structured interview techniques, documents and questionnairs. The finding indicated the basic skills of playing Yangqin including posture, techniques of playing the Yangqin, holding technique of the bamboo beater and exercising other fundamental techniques.